2020
DOI: 10.1039/c9mh01730e
|View full text |Cite
|
Sign up to set email alerts
|

Lung metastasis-targeted donut-shaped nanostructures shuttled by the margination effect for the PolyDox generation-mediated penetrative delivery into deep tumors

Abstract: A donut-shaped nanostructure effectively approaches the tumor and offers burst penetrative delivery of a large payload of drug to overcome tumor heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Within the treatment process, systemic toxicity ( Bourzac, 2014 ), drug resistance, and immune evasion ( Liu et al, 2020 ) seem to be inevitable. In this regard, nanoparticle formulation for lung cancer treatment is emerging ( Barenholz, 2012 ; Chiang et al, 2020 ), but the efficacy remains unknown ( Chen Y. et al, 2020 ). Drugs or radiotherapy ( Lang et al, 2019 ) can induce the production of excess ROS, leading to ferroptosis in lung cancer.…”
Section: Ferroptosis In Relevant Malignant Tumorsmentioning
confidence: 99%
“…Within the treatment process, systemic toxicity ( Bourzac, 2014 ), drug resistance, and immune evasion ( Liu et al, 2020 ) seem to be inevitable. In this regard, nanoparticle formulation for lung cancer treatment is emerging ( Barenholz, 2012 ; Chiang et al, 2020 ), but the efficacy remains unknown ( Chen Y. et al, 2020 ). Drugs or radiotherapy ( Lang et al, 2019 ) can induce the production of excess ROS, leading to ferroptosis in lung cancer.…”
Section: Ferroptosis In Relevant Malignant Tumorsmentioning
confidence: 99%
“…And then, Dox and poly‐ l ‐glutamic acid (PGA) were divided through cleavage of the pH‐sensitive hydrazone linker at the deep tumor site, resulting in activated Dox with high intracellular concentrations. In addition, NP‐induced extracellular leakiness (nanoEL) was induced by the disruption of the cadherin interactions as a result of the adhesion under the pressure of blood flow (Chiang, Su, Chang, Chang, & Hu, 2020). Zhongling et al reported a nano‐sized PEGylated superparamagnetic iron oxide (SPIO) NPs with anti‐EGFR monoclonal antibody (mAb) decoration for targeted delivery to EGFR‐overexpressed lung cancer.…”
Section: Deliver Drugs For Lung Cancer By Nanomaterialsmentioning
confidence: 99%
“…Recently, immune therapy held promise to suppress the metastatic cells via the cytotoxic T lymphocytes [ 6 , 7 , 8 ]. Despite the recent advance in immunotherapy, the invading clusters of metastases usually smaller than 100 mm 3 poorly performed vascularization and restricted physical contact of T lymphocytes, lowering immune responses [ 9 , 10 , 11 , 12 ]. Furthermore, the invasion of secondary tumors fills up the lymphatic vessels and reduces the space to recruit immune cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%